1998
DOI: 10.1046/j.1365-2443.1998.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic regulation of inducible nitric oxide synthase gene by CCAAT/enhancer‐binding protein β and nuclear factor‐κB in hepatocytes

Abstract: Background: Nitric oxide (NO) has diverse activities under physiological and pathophysiological conditions in many types of cells. In cultured hepatocytes, NO is produced by inducible NO synthase (iNOS) in response to interleukin (IL)-1␤. Cis-controlling elements and transcription factors which were involved in iNOS gene expression in hepatocytes have been unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 46 publications
4
40
0
Order By: Relevance
“…We reported that NF-B and CCAAT/enhancer-binding protein ␤ (C/EBP␤) synergistically activated the transcription of iNOS in hepatocytes. 45 It seems likely that hypoxia affects one of these pathways, which have a crucial role for NF-B-induced transcription in addition to its DNA binding. In the case of heat, heat inhibited the iNOS induction by preventing the degradation of I B and the NF-B DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that NF-B and CCAAT/enhancer-binding protein ␤ (C/EBP␤) synergistically activated the transcription of iNOS in hepatocytes. 45 It seems likely that hypoxia affects one of these pathways, which have a crucial role for NF-B-induced transcription in addition to its DNA binding. In the case of heat, heat inhibited the iNOS induction by preventing the degradation of I B and the NF-B DNA binding.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBPb cooperates with the p50 subunit of NF-kB on the Nur77 promoter Because the Nur77 promoter was previously shown to contain a kB element at K427 bp known to bind the NF-kB transcription factor (Pei et al 2005) and because NF-kB and C/EBPb can cooperate in other systems (Sakitani et al 1998, Montaner et al 1999, we tested whether NF-kB could activate and/or cooperate with C/EBPb on the Nur77 promoter in Leydig cells. Expression vectors encoding C/EBPb and each of the NF-kB subunits (p50 and p65) were transiently transfected in MA-10 Leydig cells along with a K1013 bp rat Nur77 reporter.…”
Section: C/ebpb Binds To and Activates The Nur77 Promotermentioning
confidence: 99%
“…Rat hepatocytes were isolated and maintained as previously described (Sakitani et al 1998). Porcine granulosa cells were prepared according to published methods (Fukuoka et al 1988).…”
Section: Cell Culturementioning
confidence: 99%
“…The transfection of hepatocytes was performed according to previously described methods (Sakitani et al 1998). Similarly, on Human 20a-HSD gene and three AKR genes q Blackwell Science Limited day 4 hCG-treated granulosa cells were transfected with 20 mg of LipofectAMINE (Life Technologies, USA), 2 mg of reporter plasmid DNA and 2 ng of pCMV-LacZ as an internal control.…”
Section: Transfection and ®Re¯y Luciferase Assaymentioning
confidence: 99%